UNRELATED CANCER OR CHEMOTHERAPY-INDUCED MALIGNANCY: A CASE OF RECTAL ADENOCARCINOMA FOLLOWED BY PLASMACYTOMA - Arifin, Fransiscus; Malonda, Franklin V. (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Proper diagnosis is the mainstay of comprehensive cancer management. However, this process is not straightforward. Some types of cancers, such as intra-abdominal cancer, are anatomically challenging to sample. Even after proper resection, the pathological diagnosis may be uncertain and requires further immunohistochemical processing. We present a rare case in which a patient with adenocarcinoma of the colon was diagnosed, surgically resected, and received chemotherapy, in which the postoperative specimen was also diagnosed as adenocarcinoma. However, after five years, he was diagnosed with plasmacytoma of the right iliac wing. Here, we discuss the possibility of unrelated secondary cancer or chemotherapy-induced malignancy.